2002
DOI: 10.1002/art.10053
|View full text |Cite
|
Sign up to set email alerts
|

Results and long‐term followup of intravenous immunoglobulin infusions in chronic, refractory polymyositis: An open study with thirty‐five adult patients

Abstract: Objective. Polymyositis is a rare inflammatory muscular disease of unknown cause. Corticosteroids and immunosuppressive drugs are the first choice of therapy but are not always effective and may cause serious side effects. Many studies have shown that polyvalent intravenous immunoglobulin (IVIG) may be of interest for the treatment of dermatomyositis. We carried out an open, prospective study to evaluate the efficacy of IVIG in subjects with polymyositis that was refractory to traditional treatments, and we ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
95
0
9

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(106 citation statements)
references
References 33 publications
(52 reference statements)
2
95
0
9
Order By: Relevance
“…It also is used in the treatment of other pregnancy complications, such as idiopathic thrombocytopenic purpura and recurrent miscarriages, and appears to be safe and well tolerated by pregnant patients (11,12). In our patient, treatment with IVIG was aimed at maintaining disease remission while decreasing the corticosteroid dosage.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It also is used in the treatment of other pregnancy complications, such as idiopathic thrombocytopenic purpura and recurrent miscarriages, and appears to be safe and well tolerated by pregnant patients (11,12). In our patient, treatment with IVIG was aimed at maintaining disease remission while decreasing the corticosteroid dosage.…”
Section: Discussionmentioning
confidence: 90%
“…IVIG therapy has been shown to be very effective in the treatment of IIMs, in particular DM, and is widely used for various autoimmune conditions during pregnancy (11). It also is used in the treatment of other pregnancy complications, such as idiopathic thrombocytopenic purpura and recurrent miscarriages, and appears to be safe and well tolerated by pregnant patients (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Eleven subjects presented esophageal disorders (including dysphagia, regurgitation and gastroesophageal reflux) evaluated with clinical assessment and manometry. In 8/11 (73%) patients they observed the complete disappearance of esophageal disorder [12].…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, long-term effects on CK levels after IVIG were reported, with 50% of patients achieving normal CK levels for more than 300 days. With regard to the longterm effects of IVIG in PM, Cherin et al [7] previously reported 35 chronic refractory cases of PM. In this study, 12 out of 25 responders to IVIG maintained full remission for 51.4 ± 13.1 months after the initial IVIG.…”
Section: Discussionmentioning
confidence: 99%